Evaluation of the Novel Centrifugal Pump, CAPIOX SL, in Chronic Large Animal Experiments. Issue 8 (12th February 2018) - Iizuka, Kei; Katagiri, Nobumasa; Takewa, Yoshiaki; Tsukiya, Tomonori; Mizuno, Toshihide; Itamochi, Yosuke; Kumano, Kouko; Tatsumi, Eisuke
Abstract: In the development of a new device for extracorporeal circulation, long‐term durability and biocompatibility are required. The CAPIOX SL Pump (SL pump, Terumo Corporation, Tokyo, Japan), which is a centrifugal pump using a two‐pivot bearing, was developed with the hope of suppressing pump thrombus formation around the bearings. This study aimed to evaluate the in vivo performance of the SL pump in the condition assumed severe clinical situation for long‐term extracorporeal membrane oxygenation (ECMO) support. Extracorporeal circulation using the SL pump was installed in three goats, with drainage from the inferior vena cava and infusion into the right jugular artery. The animals were maintained with target pump flow of 2.0–3.0 L/min for 3 or 7 days. Anticoagulation was performed by continuous infusion of heparin with a target activated coagulation time (ACT) of 200 ± 50 s. Blood tests were performed regularly. After 3 or 7 days, autopsies were performed on all animals. The pumps were disassembled and observed for thrombus formation. The results were compared with those of our previous study of the current model of the centrifugal pump (SP pump). All animals were successfully managed within target pump flows and ACT values during the scheduled period, with no adverse events. No thrombus formation was found around the bearing of the SL pump. The blood tests showed normal major organ functions, and platelet consumption and hemolysis were significantly lower in this study compared to the previous study of the SP pump. The CAPIOX SL Pump showed excellent durability and biocompatibility in a large animal experiment.